This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There's a much simpler approach to this, that is one without expanding the expression (and of course without the use of calculators).
Hints:
How is this related to the previous problems (Part 1 and Part 2)?
Does this formula look familiar ( a + b + c ) ( a + b − c ) ( a − b + c ) ( − a + b + c ) ?
See the title of this question. Why is this problem in Geometry?
The three numbers 1 3 , 6 1 , 8 0 can be found from Parts 1 and 2. Coincidence?
Please refrain from posting trivial stuff like "Press toggle latex and read the last line"
In response to the challenge master: First of all, I'm sorry for posting such trivial stuff, I will never do such stupid things in future.
And yes sir, I think this is what you were expecting:
In the other parts, we can find that the area of the triangle with sides, 1 3 , 6 1 and 8 0 was 1 4 .
We also see that, the area of that triangle using heron's formula to be 1 6 ( 1 3 + 6 1 + 8 0 ) × ( 1 3 + 6 1 − 8 0 ) × ( 1 3 − 6 1 + 8 0 ) × ( − 1 3 + 6 1 + 8 0 )
Now, multiplying the expression by 4 we get,
[ 1 6 ( 1 3 + 6 1 + 8 0 ) × ( 1 3 + 6 1 − 8 0 ) × ( 1 3 − 6 1 + 8 0 ) × ( − 1 3 + 6 1 + 8 0 ) ] × 4
But this expression is equal to 1 4 × 4 = 5 6
Therefore, 1 6 ( 1 3 + 6 1 + 8 0 ) × ( 1 3 + 6 1 − 8 0 ) × ( 1 3 − 6 1 + 8 0 ) × ( − 1 3 + 6 1 + 8 0 ) × 1 6 = 5 6
Or, ( 1 3 + 6 1 + 8 0 ) × ( 1 3 + 6 1 − 8 0 ) × ( 1 3 − 6 1 + 8 0 ) × ( − 1 3 + 6 1 + 8 0 ) = 5 6
And that leads us to a very simple approach. ⌣ ¨
EDIT: Added a square root sign and changed the value of the denominator.
Log in to reply
Check your working again, it's still wrong.
Log in to reply
Thanks sir, I have edited it. Could you please verify whether it is right?
Log in to reply
@Sravanth C. – Haha, yeah now it's right. Some tips: try to use the general form, that is replace a = 1 3 , b = 6 1 , c = 8 0 , then your working is much shorter, neater and more legible. So the readers don't have to scroll from left to right. But yeah! Good! Maybe try converting your scomment into your solution? That is, swap your solution and comments.
And don't call me sir, I'm still young, or at least I deceived myself into thinking that way.
Log in to reply
@Pi Han Goh – Thanks for your tip (sir)!
Also you can see a neat, readable and legible solution, ⌣ ¨
From the Challenge Master's hints. It is Heron's formula, where the area of a triangle is given by:
Δ = s ( s − a ) ( s − b ) ( s − c ) , where s = 1 3 + 6 1 + 8 0 , a = 2 1 3 , b = 2 6 1 and c = 2 8 0 .
And that:
− 1 6 Δ 2 = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ 0 1 1 1 1 0 c 2 b 2 1 c 2 0 a 2 1 b 2 a 2 0 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ⇒ Δ 2 = − ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ 0 1 1 1 1 0 8 0 6 1 1 8 0 0 1 3 1 6 1 1 3 0 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ = 3 1 3 6
⇒ Δ = 5 6
The idea is to use Part 1 and Part 2 which were linked in the question.
Part 1 tells us that the area is 14, and we recognize that the answer is 4 times of the area, and hence 4 × 1 4 = 5 6 .
@Chung Kevin It seems you have become a staff member. Congrats!!!
Log in to reply
Haha, that was my mistake. I was editing his profile and accidentally hit the wrong button.
Log in to reply
I wish I was that fortunate that you would hit the "make moderator" button in my profile. :P
Oops! I didn't solve part 1 and part 2, earlier.
Problem Loading...
Note Loading...
Set Loading...
Let ( a = 1 3 ) , ( b = 6 1 ) , ( c = 8 0 )
According to the question, we need to find: ( a + b + c ) × ( a + b − c ) × ( a − b + c ) × ( − a + b + c ) = ( a 2 + b 2 − c 2 + 2 a b ) × ( − a 2 − b 2 + c 2 + 2 a b )
Substituting the values of a , b and c in the above expression, we get,
( 1 3 + 6 1 − 8 0 + 2 × 1 3 × 6 1 ) × ( − 1 3 − 6 1 + 8 0 + 2 × 1 3 × 6 1 ) = ( 6 + 2 × 1 3 × 6 1 × ) ( − 6 + 2 × 1 3 × 6 1 )
Now, using ( a + b ) × ( a − b ) = ( a 2 − b 2 ) formula in the above expression, we get,
( 2 × 1 3 × 6 1 ) 2 − 6 2 = ( 4 × 1 3 × 6 1 ) − 3 6 = 3 1 7 2 − 3 6 = 3 1 3 6 = 5 6 ⌣ ¨
Here's another approach, though I posted a comment, here's a modified one(as suggested by @Pi Han Goh )
Let, a = 1 3 , b = 6 1 , c = 8 0
Therefore we need to find, ( a + b + c ) × ( a + b − c ) × ( a − b + c ) × ( − a + b + c )
From the previous questions we find that, area of a triangles with sides, a = 1 3 , b = 6 1 , c = 8 0 was 1 4 ,
Hence, 1 6 ( a + b + c ) × ( a + b − c ) × ( a − b + c ) × ( − a + b + c ) = 1 4
Now, multiplying the equation by 4 we get,
1 6 ( a + b + c ) × ( a + b − c ) × ( a − b + c ) × ( − a + b + c ) × 4 = 5 6
1 6 ( a + b + c ) × ( a + b − c ) × ( a − b + c ) × ( − a + b + c ) × 1 6 = 5 6
Finally, we can say that, ( a + b + c ) × ( a + b − c ) × ( a − b + c ) × ( − a + b + c ) = 5 6